Research on the Principle of Double Inflection Points and its Profitability - Wu, Ziyang (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Based on the price relative strength difference?P, we put forward the principle and application rules of a “Double Inflection Points” (abbreviate as DIP) model, derived fromthree different algorithms, which form three important relative strength difference moving curves and establish a new system to forecast financial trendsfrom a four-dimensional perspective. Empirical analysis shows that the DIP model evidently outperforms the single turning point models in terms of profitability, which can significantly improve predictability and profitability in financial trading.